Comments on the current taxonomy of Brachycephalus (Anura: Brachycephalidae) - Condez, Thais Helena; Monteiro, Juliane Petry De Carli; Haddad, Célio Fernando Baptista (Zootaxa, 2017)
Since the first, and simplest, description of a species of the genus Brachycephalus Fitzinger 1826, by Spix (1824), an increasing number of informative traits has been investigated to facilitate species diagnoses, including those dealing with osteology (Izecksohn 1971), sexual dimorphism in body size (Alves et al. 2006), hyperossification of the skull and skeleton (Haddad et al. 2010) and advertisement call (Garey et al. 2012), plus traits from molecular data (Condez et al. 2016). However, the recent descriptions of nine species of Brachycephalus (see Pie & Ribeiro 2015; Ribeiro et al. 2015; Bornschein et al. 2016) included inadequate diagnoses, which lacked indispensable information for any further comparisons among species. Herein, we intend to address the main flaws of these species descriptions and highlight the urgent need for a rigorous review of the genus Brachycephalus in order to assess the validity of these taxonomic proposals.